Study on the evolutionary game of the three parties in the combined medical and health-care PPP project - Zhang, Min; Yao, Ping (Frontiers in Public Health, 2023)
In the context of aging, the combination of medical and health care has become a major trend, and the introduction of PPP model into medical and health care combination projects can solve the problem of shortage of funds for the construction of medical and health care combination projects. Based on the evolutionary game theory, this paper constructs a three-party evolutionary game model of private sector-government-public to study the strategy choice of each party in the game process, and analyzes the evolutionary equilibrium strategy under different situations and the influence of the adjustment of parameter variables on the evolutionary strategy, and finds that the private sector chooses to provide high-quality services, the government chooses to actively supervise and the public chooses to actively monitor as the optimal solution. Based on the above findings, we propose corresponding suggestions and countermeasures.